Competitiveness of Milk Production. New Perspectives for Developing a New Direction in Tourism: Dairy Tourism - YERNAZAROVA, Anar; ALYONOVA, Karlygash; ANAFIYAYEVA, Zhibek; NUKESHEVA, Anar NUKESHEVA; DARIBAYEVA, Adaskhan; KIZIMBAYEVA, Azhar (Journal of Environmental Management and Tourism, 2023)
The presence of natural and economic risks in agriculture is inherent in many countries, including the Republic of Kazakhstan, which makes the development of the agricultural sector an urgent issue for agricultural producers, especially now when the integration of agro-tourism, which is a kind of breakthrough for the development of rural industry and the revitalization of rural areas, takes place. Integration of agro-ecological efficiency and agrotourism is also closely connected with the competitiveness of milk production by farms and the development of a new direction "dairy tourism", so the study of the relationship between them is of great importance for the implementation of agro-ecological quality development. Kazakhstan has favorable conditions for the development of dairy tourism sector due to the area of cultivated agricultural land, favorable natural and climatic conditions, large volume of dairy products market, positive trends in economic development of the country and, as a consequence, growth of solvent demand, which makes the dairy sector attractive. The aim of the research is to substantiate theoretical provisions and analyze the impact of agrotourism on the efficiency of dairy production competitiveness management in farms (on the example of the northern region of Kazakhstan).